PENGARUH GROWTH OPPORTUNITY DAN LIKUIDITAS TERHADAP NILAI PERUSAHAAN DENGAN STRUKTUR MODAL SEBAGAI VARIABEL INTERVENING - Hasmaynelis Fitri; Zigo Triansyah; Bayu Putra, Ramdani; Bayu Pratama Azka (MANAJEMEN, 2022)
This study aims to determine how the effect of Growth Opportunity, Liquidity on Firm Value with Capital Structure as an intervening variable. The population in this study are companies in the manufacturing sector listed on the Indonesia Stock Exchange for the period 2016-2020. While the sample in this study was obtained using purposive sampling method so that 30 companies were obtained as samples. The type of data used is secondary data taken through www.idx.co.id. The data analysis method used is panel data regression analysis. Based on the results of the study, it was concluded that partially, Growth Opportunity had a negative and significant effect on Capital Structure. Partially Liquidity has a negative and significant effect on the Capital Structure. Partially, Growth Opportunity has no effect on Firm Value. Partially, liquidity has a positive and significant effect on firm value. Partially, the capital structure has no effect on firm value. Capital structure cannot mediate the effect of Growth Opportunity on Firm Value. Capital structure can mediate the effect of liquidity on firm value